Attention Deficits and Congenital Hypothyroidism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The ability to sustain attention was studied using continuous performance tasks in 48 children with early treated congenital hypothyroidism (CH) and 35 healthy controls at the University of Groningen, The Netherlands.